PHYLOGENETIC ANALYSIS OF COLD SHOCK PROTEINS IN PSEUDOMONAS SPECIES - Sangu, Kavya; Raj, P. Vasanth; Paliwal, Neeraj; Venkateskumar, K.; Karunakaran, Rohini (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The present study focuses on the determination of the relativity of the different types of cold shock proteins. Methods: Our study was to determine the relationship among the types of CSPs. Three different strains of pseudomonas genus, Pseudomonas fluorescens, Pseudomonas aeruginosa and Pseudomonas putida were chosen and molecular profiling was performed. The sequences thus obtained were subjected to multiple sequence analysis in ClustalW database. The molecular evolution and phylogenetic study have been carried out using phylodraw. Results: The phylogenetic analysis has clearly revealed the evolutionary pattern of cold shock proteins in pseudomonas species and the current stress of mutation among the strains. Conclusion: Phylogenetic analysis of cold shock proteins has clearly shown that important conserved sequences can be very useful to study the phylogeny of bacteria.